2018
DOI: 10.1002/sim.8019
|View full text |Cite
|
Sign up to set email alerts
|

Modified power prior with multiple historical trials for binary endpoints

Abstract: Including historical data may increase the power of the analysis of a current clinical trial and reduce the sample size of the study. Recently, several Bayesian methods for incorporating historical data have been proposed. One of the methods consists of specifying a so‐called power prior whereby the historical likelihood is downweighted with a weight parameter. When the weight parameter is also estimated from the data, the modified power prior (MPP) is needed. This method has been used primarily when a single … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
70
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
7

Relationship

3
4

Authors

Journals

citations
Cited by 38 publications
(72 citation statements)
references
References 29 publications
(51 reference statements)
1
70
0
Order By: Relevance
“…29 However, none of these methods are guaranteed to control the type I error rate at the nominal 5% level. 30 While these techniques are aimed at accounting for between-study heterogeneity (which is unobserved), in the case of observed differences, for example, patient characteristics, these methods may need to be augmented either with adjustment techniques or by including the relevant patient characteristics as covariates in the statistical model.…”
Section: Appropriate Statistical Methodsmentioning
confidence: 99%
“…29 However, none of these methods are guaranteed to control the type I error rate at the nominal 5% level. 30 While these techniques are aimed at accounting for between-study heterogeneity (which is unobserved), in the case of observed differences, for example, patient characteristics, these methods may need to be augmented either with adjustment techniques or by including the relevant patient characteristics as covariates in the statistical model.…”
Section: Appropriate Statistical Methodsmentioning
confidence: 99%
“…This modification introduces the normalizing constant dependent on the weight parameter γ, 6,7 resulting in the following joint prior distribution: pc,γHBin(yCH,nCH,pc)γπfalse(pcfalse)πfalse(γfalse)Bin(yCH,nCH,pc)γπfalse(pcfalse)dpc. The denominator in Equation () is available in closed form when the prior placed on the control response rate is a Beta distribution. However, when the normalizing constant is not available in closed form it can be approximated, though this adds additional computational complexity 8 .…”
Section: Methods For Historical Control Borrowingmentioning
confidence: 99%
“…Incorporating the historical control data as a prior on the current control data allows for borrowing, and the various methods allow for different ways of introducing and modeling the possible sources of heterogeneity. The previously proposed power prior 5 , modified power prior 6,7 , and dependent modified power prior (DMPP) 8 are likelihood‐based methods that discount the historical data to account for differences between the pool of historical data and the current control data. The meta‐analytic‐predictive (MAP) prior 9 accounts for heterogeneity by assuming exchangeability among the historic and current control parameters and explicitly modeling the between‐trial variation.…”
Section: Introductionmentioning
confidence: 99%
“…The resulting posterior is analogous to a weighted average of the historic and current data. This has been extended to the use of multiple historical trials 87 …”
Section: Current Statistical Methods For Combining Current Controls Amentioning
confidence: 99%
“…This has been extended to the use of multiple historical trials. 87 Alternatively, hierarchical models explicitly model the similarity between current and historic data. For example, a meta-analysis could be used to estimate the outcome parameter and the between-study variability in the meta-analytic-predictive approach (MAP).…”
Section: Reviewmentioning
confidence: 99%